Determinants of Vessel Targeting in Vasculitis - Gary S. Hoffman (Clinical and Developmental Immunology)
Studies of autoimmune diseases have not yet elucidated why certain organs or vessels become the objects of injury while others are spared. This paper will explore the hypothesis that important differences exist in regions of the aorta that determine vulnerability to diseases, such as atherosclerosis, aortitis, giant cell arteritis and Takayasu's disease. The reader is invited to reassess; (1) whether the aorta is indeed a single homogeneous structure, and (2) whether the initial stage of aortitis (and indeed other diseases considered “autoimmune”) may be primarily due to acquired alterations of substrate, that influence unique immune profiles, which by themselves may not be pathogenic. Disease susceptibility and patterns are influenced by many factors that are inborn and acquired. Examples include genetic background, gender, ethnicity, aging, prior and concomitant illnesses, habits, diet, toxin and environmental exposures. Studies of vascular diseases must assess how such variables may affect regional differences in endothelial cells, subendothelial matrix, vascular smooth muscle and the response of each to a variety of stimuli.